2016
DOI: 10.3109/03009742.2015.1110198
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of insole use in rheumatoid feet: a randomized controlled trial

Abstract: Foot orthoses with metatarsal and medial arch supports decreases pain during walking and at rest in both feet in patients with RA. Time of insole use correlated with improvements in pain and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 24 publications
1
25
0
1
Order By: Relevance
“…Non-pharmacological interventions for RA that include foot orthoses and footwear can reduce pain and disability and improve long-term outcomes with existing and potential foot problems [8]. Previous studies have reported on the clinical effectiveness of foot orthoses in people with established RA, ranging from simple insoles to customised foot orthoses [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Non-pharmacological interventions for RA that include foot orthoses and footwear can reduce pain and disability and improve long-term outcomes with existing and potential foot problems [8]. Previous studies have reported on the clinical effectiveness of foot orthoses in people with established RA, ranging from simple insoles to customised foot orthoses [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Utilizaron plantillas con apoyo metatarsal y arco longitudinal interno y palmilla plana durante 6 meses. Determinaron que mejoraban el dolor pero no la función y la calidad de vida 14 .…”
Section: Discussionunclassified
“…Previous studies have found that insoles that are custom built to support the longitudinal and transverse arches (Hennessy et al, ; Mejjad et al, ; Moreira et al, ) as well as prefabricated, non‐customizable insoles (Cameron‐Fiddes & Santos, ) are effective in relieving pain but most studies on insoles have found no (Chalmers, Busby, Goyert, Porter, & Schulzer, ; Mejjad et al, ; Novak, Burger, Marincek, Tomsic, & Vidmar, ) or minor to moderate (van der Leeden et al, ) effects on walking. However, in our clinical experience both kinds of insoles have certain shortcomings.…”
Section: Introductionmentioning
confidence: 99%